Measuring the quality of service and the satisfaction of customers taking a rest and relax at Whitesand Resort - Phạm Xuân Lan; Nguyễn Hùng Hào (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2020)
This research aims to identify the factors contributing to the services’ quality of resorts in Vietnam. It also seeks to examine the relationship between the quality of the services and customers’ satisfaction using the survey conducted at Whitesand Resort. The result of this survey has revealed four determinants which affect the service quality, namely the empathy, the tangibles, the responsiveness and the assurance. These factors have been proven to contribute to customers’ satisfaction at the resort. Based on this result, we have come up with certain useful suggestions which can promote the development of Whitesand Resort as well as other resorts in Vietnam. It is also expected that the ideas suggested here would be of certain help for further research into the hotels and resorts industry